O papel do eixo intestino-fígado no desenvolvimento de distúrbios metabólicos associados à introdução dietética precoce de açúcares de adição e o potencial fitoterapêutico das folhas de Syzygium cumini (L.) Skeels - FREITAS, Perla Lopes de (2021)
Metabolic syndrome (MetS) is characterized by the coexistence of three or more risk factors, among the main ones we can mention: abdominal obesity, dysglycemia, hypertension, insulin resistance and dyslipidemia. The gut microbiota has been extensively investigated in the last decade due to its interaction with many metabolic pathways of the host and may be a contributing factor to many metabolic disorders. Studies show that diets supplemented with polyphenols can exert a modulating action on the gut microbiota. The Syzygium cumini (SYZ) is widely used in traditional medicine to treat metabolic disorders. Therefore, the objective of our work was to evaluate the ability of the hydroalcoholic extract (EH) rich in SYZ polyphenols to modulate the gut microbiota and its possible influence on the gut-liver axis of animals fed a high-sucrose diet. Chapter 1 of this thesis refers to a review study on the possible association between the modulation of the microbiota by polyphenols and the promotion of beneficial effects to the host through the greater production of short-chain fatty acids (SCFA). Chapter 2 presents the results of research on the effect of sucrose on glyco-lipid metabolism and on the intestinal microbiota of rats fed a high-sucrose diet after weaning. Wistar rats were fed a standard diet (CTR; n = 6) or high sucrose (HSD; n = 8) for 22 weeks. HSD animals showed an increase in TyG (13.2%), HOMA-IR (180%) and serum insulin (180%). In addition, they also showed glucose and insulin intolerance. Regarding serum lipids, the HSD group showed an increase in serum levels of TG (134.9%) and AGL (42%) when compared to CTR animals. This data is corroborated by the presence of steatosis in the liver of these animals. The high sucrose diet modified the composition of the intestinal microbiota of HSD animals, particularly associated with species of the Firmicutes phylum, which was associated with an increase in SCFA, mainly acetate. Our data show that the HSD diet was able to modify the composition of the gut microbiota, reducing bacterial diversity and favoring the growth of SCFA-producing species, promoting significant metabolic changes in the gut-liver axis of animals. Chapter 3 presents the results of research on the effect of EH on the glyco-lipid metabolism of rats fed an HSD diet in an experimental model of MetS that most resembles humans. For this, Wistar rats were fed standard diets (CTR) or high in sucrose (HSD) for 17 weeks. After this period, the HSD animals were divided into 3 groups: HSD treated (v.o) with EH at doses of 0.25 g / Kg or 0.5 g / Kg (for 5 weeks) and untreated HSD. The treatment with HE in both doses reduced the fasting GL of the HSD group when compared to untreated animals. This effect was corroborated with reductions in TyG and attenuation of intolerances to GL and insulin in animals treated with HE. The improvement in insulin sensitivity was corroborated by the increase in the hepatic glycogen content in the treated animals. EH was able to decrease TG around 40%, in the two doses evaluated, and to reverse non-alcoholic fatty liver disease (NAFLD). However, EH was not able to modulate the intestinal microbiota, which was totally modified by the high-sucrose diet. Thus, the traditional use of this plant in the control of glycemic homeostasis and, for the first time, the ability of HE to reverse hypertriglyceridemia and hepatic steatosis in a human like MetS model are confirmed. However, the mechanism by which EH improves these metabolic parameters does not involve modulation of the gut microbiota.